Life Skill For Women Empowerment: Patchwork For Creativity And Entrepreneurship - laela Hikmah Nurbatra; Hartono Hartono (Jurnal Perempuan dan Anak, 2020)
The present community service highlights life skill program for women empowerment. Particularly, the current community empowerment program involves members of PKK of RT 03 RW 02 Sumbersekar, Dau Malang. There are currently 32 members in the organization that comes from different socio-economic background. In terms of entrepreneurial skills, the women in the particular organization have limited knowledge and skill in entrepreneurship. Based on the observation and confirmed with the result of interview, most of the women who are the member of PKK RT 03 RW 02 are low-middle class family who rely on the husbands’ income from farming. Given that most of the members relies on agricultural sector as their income, most of them do not have a sufficient educational background. Although the community has issue with limited fund to support their program, they have a good creativity. In addition, given that the Gender Empowerment Index in East Java is still low, the present community empowerment program intends to offer solution to empower the women at PKK RT 03 RW 02 Sumbersekar with the expectation that it will not only provide more space for their creativity but also their financial support. In accordance to that, the present community service program is not only aims to empower the women, but also improve their economics. The results indicated that the program ran successfully although it was conducted in the COVID 19 pandemic. Some adjustments have been made, but it did not change the fact the target communities obtained the positive effect from the empowerment program.